2-Methyl-3-(3-methylphenyl)acrylic acid - Muhammad, Niaz (International Union of Crystallography, 2008)
The crystal structure of the title compound, C(11)H(12)O(2), consists of dimers which are formed due to intermolecular O—H⋯O hydrogen bonding. The dimers are linked to each other by C—H⋯O hydrogen bonds, where C—H belongs to the benzene ring and the O atom is of a carbonyl group of an adjoining molecule. There exist two intermolecular C—H⋯O hydrogen bonds which form five-membered rings. There exist two π–π interactions between the benzene rings. The perpendicular distance in these interactions are 3.006 and 3.396 Å. There also exist C—H⋯π and C—O⋯π interactions.